Analysis of Big Data and Quality-of-Experience in High-Density Wireless Network - Qaiyum, S. (Institute of Electrical and Electronics Engineers Inc., 2016)
The proliferation of smart devices, along with the availability of bandwidth-intensive applications are generating huge volumes of data that create challenges to IT industries. Data handling becomes more troublesome when mobile user's gather in tens and thousands of quantity at confine locations and generates Big Data. Analysis and storing of this huge, varied and complex data put great challenges to the Network Service Providers (NSP). Thus, service providers are facing problems in managing big data in dense environment and maintaining user's Quality of Experience (QoE). However, big data also provide great opportunities to NSP. The accurate analysis of big data in real-time reveals the user experience of network services which helps the service providers to take timely action to improve user QoE. Thus, this paper presents an overview of Big Data and QoE in High-Density Wireless Network (HDWN) environment. Â© 2016 IEEE.